Pengaruh Penggunaan E-Modul Flipbook Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPA di Tingkat Sekolah Dasar - Umami, Jazilia; Prayogo, Muhammad Suwignyo (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to determine the effect of using the flipbook E-module on student learning outcomes in science subjects at the elementary school level. This research uses a qualitative approach, which describes and analyzes the effect of using the flipbook E-module on student learning outcomes in science subjects at the elementary school level. The data collection technique used in this research is library research where literature study is literature research, which is the practice of collecting research-related materials from books, scientific journals, literature, and other publications that are worthy of being used as sources for research that will be researched by the author, by describing and analyzing the data. A research variable is everything that the researcher chooses to study in order to study it further, collect data about it, and then draw conclusions. In this study, it used Independent Variables and Dependent Variables. Harapan uses a qualitative approach to provide information about the facts of the effect of using the E-module flipbook on student learning outcomes in science subjects at the elementary school level. The purpose of writing this article is to increase readers' knowledge about the importance of using the flipbook E-module to student learning outcomes in science subjects at the elementary school level.